A comparative study for tidal current velocity prediction using simplified and fast algorithms. (November 2020) - Tondut, J.; Tawil, T. El; Thiébot, J.; Guillou, N.; Benaouicha, M.
Abstract: Interest in marine renewable energies has grown in recent years, especially in northern European shelf seas where several technological devices have been developed. In this context, numerous investigations focused on accurate predictions of tidal currents and their respective kinetic energy. An empirical estimation of the current velocity is explored in this study, where three different methods are presented. The first method is a linear approximation of the tidal vector velocity as a function of the tidal coefficient (ratio of the tidal range over its maximal value). The second and the third methods are a piece-wise linear and an exponential relationships between tidal vector velocity and the tidal coefficient, respectively. These three methods are compared to reference values obtained using a numerical simulation of tidal hydrodynamics. These methods are applied at two prominent tidal stream energy sites along the coast of France, the Fromveur Strait (western Brittany) and the Alderney Race (between the island of Alderney, Channel islands, and the Cap de la Hague, France). Results show that the piece-wise linear and the exponential models are more accurate than the linear approximation, where the mean error decreased by 12.7% and 14.9% respectively at the worst case scenario.